Análise de fornecedores de um setor público empregando o método Fuzzy-TOPSIS com auxílio do método AHP - Guillet, Vinicyus Mourão Monteiro (2019)
Choosing suppliers is among the most complex tasks for a manager because of the many possible variables involved in that decision making. Analyzing criteria such as quality, delivery time and price can currently influence the administrative efficiency of an institution or an organization. However, it is necessary to develop methods, techniques and mechanisms that support the purchasing manager to achieve the best decision, since making decisions, where there are many aspects to be analyzed, is not feasible. Therefore, this study aims to use the Fuzzy-TOPSIS method with the aid of the Analytic Hierarchy Process, which are multicriteria analysis techniques. The use of these methods aims to simulate, for a sector of a public institution in the central region of the state of Rio Grande do Sul, a model that assists in choosing the best supplier of a particular chemical reagent. This work, besides presenting a model of decision making that can be used in purchases of other products, expresses the great importance of simulating decision methods previously to be definitively placed in the market. The results showed that the definition of the criteria by the AHP obeyed the condition of consistency and can be used as supplier selection criteria. In the Fuzzy-TOPSIS Method, the results expressed that the Supplier Reputation criterion has a value of 2.75, which shows that it is the criterion that weighs the most important for the classification of the best suppliers for the reagent, taking into account which directly influences the worst supplier's . The preference survey ratified the calculations, showing that both the use of the methods and the results obtained in the preference search, the same supplier was the best ranked.